A GENERAL EQUATION OF STATE FOR SUPERCRITICAL FLUID MIXTURES AND MOLECULAR DYNAMICS SIMULATION OF MIXTURE PVTX PROPERTIES - Duan Z.; Moller N.; Weare J.H. (My University, 1996)
A general Equation of State (EOS), which we previously developed for pure nonpolar systems, is extended to polar systems such as water and to mixtures in this study. This EOS contains only two parameters for each pure component and two additional parameters for each binary mixture (no higher order parameters are needed for more complicated mixture systems). The two mixing parameters can be eliminated for nonaqueous mixtures with a slight loss of accuracy in both total mole volume and in excess volume (or nonideal mixing). Comparison with a large amount of experimental PVTX data in pure systems (including H2O) and in the mixtures, H2O-CO2, CO2-N2, CH4-CO2, and N2-CO2-CH4 results in an average error of 1.6% in density. Comparison with commonly used EOS for supercritical fluids shows that the EOS of this study covers far more T-P-X space with higher accuracy. We believe that it is accurate from supercritical temperature to 2000 K and from 0 to 25,000 bar or higher with an average error in density of less than 2% for both pure members and mixtures in the system H2O-CO2-CH4-N2-CO-H2-O2-H2S-Ar and possibly with additional gases. Comparison with the published simulated data suggests that this EOS is approximately correct up to 300,000 bar and 2800 K.We also simulated the PVTX properties of a number of supercritical fluid mixtures using molecular dynamics (MD) simulation. These results and those of other authors are well predicted by the EOS of this study.